Image-Based Models for Left Heart Flow Morphodynamics in Hypertrophic Obstructive Cardiomyopathy - Sultan, Abdelrahman A (AUC Knowledge Fountain, 2025)
Relieving flow obstruction in hypertrophic obstructive cardiomyopathy is highly effective in reducing symptoms and promoting left ventricular remodeling. However, existing characteristics in the disease, such as the systolic anterior motion of the mitral, mitral regurgitation, and papillary muscle motion, and their effect on ventricular flow and vortex formation, have not been thoroughly addressed. This study aims to develop image-based computational fluid dynamics models to evaluate flow morphodynamics in hypertrophic obstructive cardiomyopathy. A computational fluid dynamics model is constructed to investigate the interaction between inflow and outflow in hypertrophic obstructive cardiomyopathy, with a focus on how the motion of the left ventricular wall influences the flow dynamics in the aortic root and valve. The findings highlight the importance of the Venturi effect in LVOT, the critical role of wall shear stress in the aortic valve and LVOT, and the need for improved preoperative strategies in septal myectomy interventions. Then a more efficient computational fluid dynamics is developed that utilizes spatiotemporal magnetic resonance data to investigate unusual flow patterns in the left heart in hypertrophic obstructive cardiomyopathy with inflow abnormalities, shedding light on alterations in flow morphodynamics. This has been achieved by employing a velocity mapping algorithm along with integrating 4D-CT-derived wall motion information, resulting in a significant reduction in analysis time. The research highlights the significant impact of wall shear stress due to mitral valve regurgitation on the left atrium, suggesting its role in structural changes and decreased mobility. Further enhancement of these frameworks may advance the understanding and modeling of cardiac flow dynamics, possibly helping in clinical decision-making.